Pengaruh Senam Hamil Terhadap Pengurangan Nyeri Punggung Pada Ibu Hamil Trimester III Di Praktik Mandiri Bidan Zaihana Muharamah Kota Bengkulu Tahun 2026 - Dela Senja Marlini; Kintan Anissa; Meri Epriana Susanti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Based on global data, the WHO reports that 50–70% of pregnant women experience back pain during pregnancy, with an average prevalence of 56% (BMC Pregnancy & Childbirth, 2023). In Indonesia, the Basic Health Research (Riskesdas) indicates that back pain is still a common complaint among pregnant women, while the 2022 Indonesian Health Profile recorded a maternal mortality rate of 189 per 100,000 live births (Ministry of Health, 2023). The purpose of this study was to determine the effect of prenatal exercise on reducing back pain in pregnant women in their third trimester. The method used was a pre-experimental design using a one-group pre-post test approach. The sampling technique used total sampling, with a sample size of 18 pregnant women in their third trimester. Back pain levels were measured using a numeric pain rating scale before and after the prenatal exercise intervention. Data were analyzed univariately and bivariately using the Wilcoxon Signed Rank Test. The results of the univariate analysis of back pain before prenatal exercise revealed that the majority of respondents experienced moderate back pain, 12 respondents (66.7%). After prenatal exercise, almost all respondents experienced a reduction in back pain, with 17 (94.4%) experiencing mild pain. Bivariate analysis showed an effect of prenatal exercise on reducing back pain in pregnant women in the third trimester, with a p-value of 0.001 (p < 0.05). The researchers recommend that healthcare workers, particularly midwives at the Zaihanna Muharamah Midwife Independent Practice, provide regular education and support to pregnant women regarding prenatal exercise as a non-pharmacological intervention to reduce back pain and increase comfort during pregnancy.